Study on the Role of Aquatic Plants and Rhizospheric Microorganisms in Constructed Wetlands in Domestic Wastewater Treatment - Nguyen, Minh Phuong; Nguyen, Thi Loan; Do, Thi Hang; Do, Thi My Luong; Pham, Lan Thi; Nguyen, Thi Hong Nhung (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Biological method using aquatic plants for domestic wastewater treatment is being  applied widely due to high treatment efficiency and low cost. The aim of the study is to evaluate the role of aquatic plants and microorganims associated with  the roots of different wetland plants ( Cyperus , Dracaena sanderiana, Lemna minor, Pistia stratiotes and Eichhornia crassipes ) in constructed wetlands receiving the same domestic wastewater source. The physico-chemical parameters of the wastewater and the number of microorganisms were determined at different retention times: 0, 7, 14, 21, 28 and 35 days. The results showed that the aquatic plants and microorganisms were capable of reducing the concentrations of pollutants in the wastewater. Also,  the number of bacteria increased according to  the retention time and the highest number of bacteria was found in the roots of Pistia stratiotes at 65 x 10 9 CFU/g after 35 days of the experimental period. The ammonium treatment efficiency of the Pistia stratiotes system was highest after 35 days (99.1%).